(untitled) (The Research of Medical Science Review, 2025)
Objective: To compare the hearing outcome of ossiculoplasty in terms of Air-Bone Gap closure using auto graft vs. alloplastic in Chronic Suppurative Otitis Media patients. Study Design: Randomized control Study Study Duration: 06 months Study Place: Capital Hospital, CDA Hospital, Islamabad Methods: A consecutive non probability sampling technique was used and sample size of 60 individuals was calculated using open EPI Calculator. The individuals were divided into two equal groups. Patients in group A underwent Ossicular reconstruction using autograft (incus) and group B underwent Ossicular reconstruction using alloplastic material (fluoroplastic). Patient in both groups were assessed using Pure Tone Audiometry (PTA) preoperatively and postoperatively at 1st and 2nd month to compare air bone gap closure. The data was entered and analyzed using SPSS 23.0 Results: In our study, total 60 patients were included, among them 28 were males and 32 were females. Patients had been divided into 02 equal groups. At start of study, AB gap in group A was 27.7±7.9 and in group B was 29.4±7.9. When compared at 1st month, AB gap in group A was 22.6±8 and in group B was 26.3±7.5 and when seen at 2nd month, it was 19.1±8.1 in group A and 23.8±7.7 in group B. There was also significant improvement in parameters like vertigo and tinnitus in group A as compared to the group B. Conclusion: From our study, we concluded that autologous incus grafts carried superior prognosis as compared to allografts.